SHAMANEN, JOMFRUEN OG SKATTEVÆSENET: Portræt af en mirakelmager fra det sydlige Chile - Kristensen, Dorthe Brogaard (Tidsskriftet Antropologi, 2008)
This article presents the case of the shaman José Karipan, who is considered one of the most powerful and popular shamans in southern Chile. The article explores the success of his practice as a healer, by analyzing the relationship between healing, identity and the socio-economic and political context of Southern Chile. It is argued that shamanistic medical practice is so popular among patients in Southern Chile due to its sensitivity to their historical past and socio-political reality. The shaman’s practice and figure build upon symbols and aspects of his social environment; the shaman is Roman Catholic and claims to receive his healing power from the Virgin of Carmen, the national saint of Chile. Furthermore, he is publicly known for a conflict with the local taxation authorities, who accuse him of failing to claim tax for his income as a healer. These factors serve to challenge the logic of the Chilean state but also show how the shaman’s personal practices are embedded inside the logic of the state, and draw upon national symbols as a source of power.